2011
DOI: 10.1074/jbc.m111.277376
|View full text |Cite
|
Sign up to set email alerts
|

Yeast ADP/ATP Carrier Isoform 2

Abstract: Background: ADP/ATP carrier (Ancp) is a model of mitochondrial carriers that mediates the transport of metabolic intermediates. Results: Yeast Ancp exhibits inhibitor-dependent solvent accessibility. Ancp signature sequence is involved in the ADP/ATP binding step. Conclusion: Ancp has a highly dynamic structure, with different protein parts acting in synergy. Significance: Learning the functional dynamics of Ancp is crucial for understanding ADP/ATP transport mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The TP4 peptide structure and predicted ANT2 model were uploaded to the GRAMM-X docking server, which was used to perform a rigid body procedure. In the interface residue constraints fields, we restricted the receptor binding sites to the RRRMMM signature sequence from Arg235 to Met240, which is located at the bottom of the cavity and is expected to be involved in ADP/ATP binding [ 44 ]. All ADP/ATP carriers exhibit the RRRMMM consensus sequence, and this motif is highly conserved in ANTs across species [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TP4 peptide structure and predicted ANT2 model were uploaded to the GRAMM-X docking server, which was used to perform a rigid body procedure. In the interface residue constraints fields, we restricted the receptor binding sites to the RRRMMM signature sequence from Arg235 to Met240, which is located at the bottom of the cavity and is expected to be involved in ADP/ATP binding [ 44 ]. All ADP/ATP carriers exhibit the RRRMMM consensus sequence, and this motif is highly conserved in ANTs across species [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the evidence that ANT1 is a central point of control for oxidative metabolism and that mutations in ANT1 in yeast 31 and humans 32 can cause profound dysfunction, we focused on characterizing the biophysical mechanisms by which ANT1 function might be altered by acetylation of these charged residues. Acetylation of critical positively charged residues of ANT1 could affect the electrostatic properties and inhibit the initial capture or binding of ADP or could perturb its structure or dynamics, possibly changing the shape of its binding pocket or altering molecular dynamics that facilitate ligand recognition or channel opening.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six arginines identified, three are part of the RRRMMM motif, characteristic of all ADP/ATP transporters. 31 Another two mutant arginines in yeast correspond to Arg80 and Arg280 in the human transporter, which bind ADP and flank Lys23 in the bovine crystal structure. Finally, the single most critical lysine in yeast, Lys38, is in a region with a sequence almost identical to that of the regions surrounding Lys23 in human ANT1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study of yeast Aac2 using hydrogen/deuterium exchange-mass spectrometry showed that the BA-bound Aac2 is structurally different from the CATR-bound form. The BA conformation has better solvent accessibility from the matrix side [26, 27]. Ant has the RRRMMM signature sequence, which is absent from other mitochondrial carriers.…”
Section: Physiological Roles Of Adenine Nucleotide Translocasementioning
confidence: 99%
“…This motif spans over the thinnest part of the channel and the arginine residues are essential for attracting the negatively charged nucleotides to facilitate transport [25, 28, 29]. In addition to the arginine residues, the methionine triplet also contributes to nucleotide translocation or binding [27]. …”
Section: Physiological Roles Of Adenine Nucleotide Translocasementioning
confidence: 99%